Connections : Knowledge Notes from the Transport and ICT Global Practice - World Bank (Washington, DC, 2017)
Connections is a series of concise knowledge notes from the World Bank Group’s Transport and ICT Global Practice. Connections discusses projects, experiences, and front-line developments in Transport and ICT. This set includes notes from 2015 and 2016.